2016
DOI: 10.15403/jgld.2014.1121.252.off
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Sustained Off-Therapy Response to Sorafenib in Advanced Hepatocellular Carcinoma

Abstract: A 75-year-old Caucasian woman with alcohol-related cirrhosis was admitted to our Unit in October 2012 for the diagnostic evaluation of a focal liver lesion detected by regular surveillance ultrasound. Her medical history included heavy smoking (about 40 cigarettes/ day), hypertension, and chronic obstructive pulmonary disease diagnosed several years before.Upon admission the patient was asymptomatic and there was no evidence of hepatic encephalopathy, ascites or peripheral edema. Physical examination was unrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Characterizing the biological peculiarities of the tumor could help the identification of those characteristics that make one histological type more responsive to Sorafenib than another. However, according to the available guidelines [6,10], the diagnosis of HCC is based on the vascular behavior of lesions greater than one centimeter on imaging, whereas biopsies on HCC are less and less carried out, thus limiting biomarkers' evaluation as for the present report [11]. Recent studies have demonstrated that several biomarkers may help to predict a poor response to Sorafenib, such as a fast reduction in serum AFP while des-y-carboxyprothrombin levels following treatment predicts a good response to Sorafenib [12].…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing the biological peculiarities of the tumor could help the identification of those characteristics that make one histological type more responsive to Sorafenib than another. However, according to the available guidelines [6,10], the diagnosis of HCC is based on the vascular behavior of lesions greater than one centimeter on imaging, whereas biopsies on HCC are less and less carried out, thus limiting biomarkers' evaluation as for the present report [11]. Recent studies have demonstrated that several biomarkers may help to predict a poor response to Sorafenib, such as a fast reduction in serum AFP while des-y-carboxyprothrombin levels following treatment predicts a good response to Sorafenib [12].…”
Section: Discussionmentioning
confidence: 99%
“…Its three-dimensional imaging technology enables physicians to view liver blood vessels and lesions that are more solid, clear, more accurate, and more comprehensive; allowing a reasonable needle puncture and optimizing the freezing effect[11,29,45,46]. Its rapid scan imaging during surgery allows the detection of the formation of ice ball and freezing conditions, provides an accurate lesion and surrounding tissue image, help in the timely adjustment of the ablation procedure, and prevents damage in surrounding tissues, while improving the effectiveness of tumor tissue ablation[9,35,47]. …”
Section: Discussionmentioning
confidence: 99%
“…The recommended guideline of ablation is to destroy cancerous lesions with a normal tissue circumferential safety margin of 5 mm to 10 mm to make sure that the whole lesion is treated [10,33]. After thermal ablation of a tumour, a hyperaemic rim appears which surrounds the ablated area [11,12]. The rim is not visible on grey-scale US, but contrast CT, MRI and CEUS show this rim as uniform, homogeneous, larger than the initial lesion in benign tumours, and irregular, with a size similar to the initial cancerous lesion if the ablation is not complete [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…This is the zone where few cancer cells might escape heat leaving behind a residual tumour which consequently causes local recurrence. After ablation, the reactive tissue inflammation is shown as a hyperaemic rim surrounding the ablated zone [9,12]. This rim makes it difficult to differentiate between complete ablation and residual tumour [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation